Evaluation Of Accounting Information System Security For Fixed Asset Procurement That Supported By Internal Control System At The Head Office Of PT. Bank SulutGo - Millenia R. Pangaila; Stanly W. Alexander; Meily Y. B. Kalalo (Universitas Sam Ratulangi, 2022)
ABSTRACT Accounting information systems for fixed asset procurement are prone to security risks that could interfere with the system. Due to the security procedures of accounting information systems, the procurement of fixed assets is protected from potential risks and threats in the operations, equipment, and associated data. This study aims to comprehend the security of the accounting information system supported by internal control and how it protects the accounting information system for procurement of fixed assets from the threats and risks at PT. Bank SulutGo’s head office, and compare it with existing theories. This qualitative research applies a descriptive qualitative method to analyze the data. The result indicated that the accounting information system security at PT. Bank SulutGo’s head office for the procurement of fixed assets is quite adequate, as proven by the procedure control activities that align with the theory. However, through data processing, there is still a weakness in internal control activities. Due to the lack of a backup archive, the internal control activities can not fully guarantee the security of the accounting information system for purchasing fixed assets at PT. Bank SulutGo’s head office. Thus, a backup archive must be created so the internal control operations can optimally support the security of the accounting information system for the procurement of fixed assets